A LINEAR PROGRAMMIMG MODEL FOR TIDAL RIVER WATER QUALITY MANAGEMENT - N. Inyim; W. Liengcharernsit (International Association of Lowland Technology, 2012)
This paper presents the formulation of a mathematical model for tidal river water quality management, considering tidal effect on pollutant transport in a tidal river. The linear programming optimization and finite element method are used in model formulation. The objective function of the model is to maximize total BOD load which can be discharged into the river. The decision variables are the ratio of remaining BOD after treatment to the generated BOD of all controllable sources of BOD load discharging into the tidal river. The BOD and DO constraint inequalities are formulated such that at any time step the BOD values at identified nodal points are not more the specified limits and the DO values are not less than the specifies limits. Since the objective function and all the constraints are linear functions, this optimization problem is in the form of linear programming and the well known Simplex method can be used to solve the problem. To demonstrate the application of the model, it is applied to determine the optimal management plan for allocating the degree of treatment among the central wastewater treatment plants of large municipalities located along the Thachin river in the central region of Thailand. The construction plan includes seven wastewater treatment plants located at different sites along the river. This case study can demonstrate effectiveness of the model in determining the optimal water quality management plan for a tidal river and providing the optimal solution for wastewater management.